Un mare poet al limbii române - Ion Brad (Revista de Istorie și Teorie Literară)
With the occasion of Fănuş Neagu’s 75th anniversary, Ion Brad, a writer, ambassador and theatre director, collected all the dedications received from his friend on his books during many years.